Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Absolutely! To find a function rule that matches the given table of values, we start by noting the pairs of \((x, y)\) values:
[tex]\[ \begin{align*} (3, 13), \\ (5, 31), \\ (7, 57), \\ (9, 91). \end{align*} \][/tex]
We aim to find a polynomial function of the form:
[tex]\[ y = ax^2 + bx + c \][/tex]
We will determine the coefficients \(a\), \(b\), and \(c\).
### Step-by-Step Solution
1. Set up a system of equations:
For each pair \((x, y)\), substitute the values into the polynomial equation:
[tex]\[ \begin{align*} 13 &= a(3)^2 + b(3) + c, \\ 31 &= a(5)^2 + b(5) + c, \\ 57 &= a(7)^2 + b(7) + c, \\ 91 &= a(9)^2 + b(9) + c. \end{align*} \][/tex]
2. Expand and simplify:
[tex]\[ \begin{align*} 13 &= 9a + 3b + c, \\ 31 &= 25a + 5b + c, \\ 57 &= 49a + 7b + c, \\ 91 &= 81a + 9b + c. \end{align*} \][/tex]
3. Solve the system of equations:
Solving the above system, we find:
[tex]\[ a = 1, \quad b = 1, \quad c = 1 \][/tex]
### Final Function Rule
From the coefficients obtained, the polynomial function that matches the given table of values is:
[tex]\[ y = x^2 + x + 1 \][/tex]
### Verification
Let's verify by substituting each value of \(x\) back into the function:
1. For \(x = 3\):
[tex]\[ y = 3^2 + 3 + 1 = 9 + 3 + 1 = 13 \][/tex]
2. For \(x = 5\):
[tex]\[ y = 5^2 + 5 + 1 = 25 + 5 + 1 = 31 \][/tex]
3. For \(x = 7\):
[tex]\[ y = 7^2 + 7 + 1 = 49 + 7 + 1 = 57 \][/tex]
4. For \(x = 9\):
[tex]\[ y = 9^2 + 9 + 1 = 81 + 9 + 1 = 91 \][/tex]
Therefore, the function rule [tex]\(y = x^2 + x + 1\)[/tex] correctly matches the given table of values.
[tex]\[ \begin{align*} (3, 13), \\ (5, 31), \\ (7, 57), \\ (9, 91). \end{align*} \][/tex]
We aim to find a polynomial function of the form:
[tex]\[ y = ax^2 + bx + c \][/tex]
We will determine the coefficients \(a\), \(b\), and \(c\).
### Step-by-Step Solution
1. Set up a system of equations:
For each pair \((x, y)\), substitute the values into the polynomial equation:
[tex]\[ \begin{align*} 13 &= a(3)^2 + b(3) + c, \\ 31 &= a(5)^2 + b(5) + c, \\ 57 &= a(7)^2 + b(7) + c, \\ 91 &= a(9)^2 + b(9) + c. \end{align*} \][/tex]
2. Expand and simplify:
[tex]\[ \begin{align*} 13 &= 9a + 3b + c, \\ 31 &= 25a + 5b + c, \\ 57 &= 49a + 7b + c, \\ 91 &= 81a + 9b + c. \end{align*} \][/tex]
3. Solve the system of equations:
Solving the above system, we find:
[tex]\[ a = 1, \quad b = 1, \quad c = 1 \][/tex]
### Final Function Rule
From the coefficients obtained, the polynomial function that matches the given table of values is:
[tex]\[ y = x^2 + x + 1 \][/tex]
### Verification
Let's verify by substituting each value of \(x\) back into the function:
1. For \(x = 3\):
[tex]\[ y = 3^2 + 3 + 1 = 9 + 3 + 1 = 13 \][/tex]
2. For \(x = 5\):
[tex]\[ y = 5^2 + 5 + 1 = 25 + 5 + 1 = 31 \][/tex]
3. For \(x = 7\):
[tex]\[ y = 7^2 + 7 + 1 = 49 + 7 + 1 = 57 \][/tex]
4. For \(x = 9\):
[tex]\[ y = 9^2 + 9 + 1 = 81 + 9 + 1 = 91 \][/tex]
Therefore, the function rule [tex]\(y = x^2 + x + 1\)[/tex] correctly matches the given table of values.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.